Patrystyczne początki kultu eucharystycznego poza Mszą - Królikowski, Janusz (Vox Patrum, 2023)
This article discusses the question of the beginnings of the devotion to Eucharist outside the time of the Mass, except for the Viaticum which belongs to the continuous tradition of the Church. The aim of the paper is to answer the question whether and in what extent this matter is present in the writings of the Church Fathers as well as in Church practice in the first millennium. There can be seen a slow but progressive appearance of certain cultic forms which clearly draw the attention to the need for a wide perspective on Eucharist in the overall Christian life, although they have not yet transformed into a proper devotion. Nevertheless, it can be argued that numerous questions concerning the Eucharist, in the context of different spiritual phenomena, require larger attention form theologians.